1997
DOI: 10.1002/(sici)1097-0215(19970502)71:3<476::aid-ijc28>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Transfection of the gene for B7-1 but not B7-2 can induce immunity to murine malignant mesothelioma

Abstract: Transfection of the genes encoding the co-stimulatory molecules B7-1 and B7-2 has enhanced the development of immunity to a variety of experimental tumors, although most of these were inherently immunogenic. We have determined the effect of expression of these genes on the induction of immunity to 2 non-immunogenic murine malignant mesothelioma (MM) cell lines (AC29 and AB1). We had previously shown that B7-1 transfection into AC29 delayed but did not prevent tumor development by certain of the transfectant cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…7,10,11,21 As control transfectants, tumor cells were transfected with the phb -Apr-neo vector alone and maintained as described above.…”
Section: Dna Constructs and Transfection Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…7,10,11,21 As control transfectants, tumor cells were transfected with the phb -Apr-neo vector alone and maintained as described above.…”
Section: Dna Constructs and Transfection Proceduresmentioning
confidence: 99%
“…3,4 More recent treatment strategies for solid tumors such as MM, particularly gene therapy and immunotherapy, have shown some promise in both human 5,6 and murine studies. Several cytokines, including IL -2, 7,8 GM -CSF, 9 B7 -1, 10,11 IL -12, 12 IFN -, 13,14 and IFN - 15 have demonstrated significant antitumor effects. However, the delivery of these cytokines has been problematic, which has limited the use of these cytokines in clinical practice, hence the need for gene therapy approaches that aim to improve cytokine delivery.…”
mentioning
confidence: 99%
“…31 Furthermore, transduction of B7-1 but not of B7-2 was effective in previous studies of mesothelioma. 13 This study examined the ability of a fowlpox vector encoding the TRICOM construct, which encodes for costimulatory molecules B7-1, ICAM-1, and LFA-3, to stimulate anti-mesothelioma immunity. Tumor cells modified to express high levels of these costimulatory molecules can activate T cells to a greater extent than tumor cells transduced with any one or two of these molecules.…”
Section: Discussionmentioning
confidence: 99%
“…12 Expressing the costimulatory molecule, B7-1 (CD80), in a nonimmunogenic mesothelioma tumor enhances the generation of tumorspecific CTL with consequent inhibition of tumor development. 13,14 More recently, combinations of 3 costimulatory molecules, B7-1, ICAM-1 (CD54) and LFA-3 (CD58), have been shown to activate T cells to a far greater extent than the combination of 1 or 2 costimulatory molecules. This triad of costimulatory molecules, also known as TRICOM, has been encoded in recombinant pox viral vectors and has been shown to significantly enhance antitumor immune responses in mouse colon cancer and lymphoma models.…”
mentioning
confidence: 99%
“…Earlier studies in animals revealed that tumor cells modified to express B7.1 costimulatory molecules had enhanced immunogenicity and were capable of inducing immune responses in naive animals that could protect against challenge with unmodified tumor cells. [11][12][13][14][15][16][17] Introduction of B7.1 into several human tumor lines also improved their immunogenicity in vitro and in some cases led to activation of specific CTL. [18][19][20][21][22][23][24][25] …”
Section: Introductionmentioning
confidence: 99%